Bis-Cyclometalated Indazole and Benzimidazole Chiral-at-Iridium Complexes: Synthesis and Asymmetric Catalysis - Brunen, Sebastian (Molecules, 2021)
A new class of bis-cyclometalated iridium(III) catalysts containing two inert cyclometalated 6-tert-butyl-2-phenyl-2H-indazole bidentate ligands or two inert cyclometalated 5-tert-butyl-1-methyl-2-phenylbenzimidazoles is introduced. The coordination sphere is complemented by two labile acetonitriles, and a hexafluorophosphate ion serves as a counterion for the monocationic complexes. Single enantiomers of the chiral-at-iridium complexes (>99% er) are obtained through a chiral-auxiliary-mediated approach using a monofluorinated salicyloxazoline and are investigated as catalysts in the enantioselective conjugate addition of indole to an α,β-unsaturated 2-acyl imidazole and an asymmetric Nazarov cyclization.